Observations on the Biology of Afrotropical Hesperiidae (Lepidoptera). Part 8. Hesperiinae incertae sedis: Dracaena Feeders - Cock, Matthew J. W.; Congdon, T. Colin E.; Collins, Steve C. (Zootaxa, 2015)
The Afrotropical genera Gamia and Artitropa are only known to feed on species of Dracaena (Asparagaceae), and together with Leona lissa Evans, which may require a new genus, they are the only Afrotropical Hesperiidae that feed on this unusual host genus. We present partial life histories of two species of Gamia, 22 taxa of Artitropa (of at least 12 species, and including several undescribed taxa), and notes on the life history of L. lissa. Based on life history information, Gamia and Artitropa are considered likely to form a monophyletic group, probably most closely related to some of the palm-feeding genera currently placed incertae sedis, but formerly in Evans’ 1937 Ploetzia group of genera. Notes on natural enemies of A. erinnys (Trimen) and A. milleri Evans are included.